The Addition of Copper Nanoparticles to Mineral Trioxide Aggregate for Improving the Physical and Antibacterial Properties - Muhammad Akram Fakhriza; Bambang Rusdiarso; Siti Sunarintyas; Nuryono Nuryono (Universitas Gadjah Mada, 2023)
The physical and antibacterial properties of mineral trioxide aggregate (MTA) have been improved by adding copper nanoparticles (CuNP). The CuNP colloid was synthesized by reacting CuCl2·2H2O and NaBH4 as the reducing agent using C6H8O6 as the capping agent. The Cu(II) concentration was varied by 3.0, 6.0, and 9.0 mM to produce CuNP-3, CuNP-6, and CuNP-9 colloids, respectively. The CuNP colloids were characterized with a UV-Vis spectrophotometer and TEM. MTA was hydrated with CuNP at a mass-to-volume ratio of 2:1 to produce Cu-MTA-3, Cu-MTA-6, and Cu-MTA-9, respectively. All products were characterized with XRD and SEM-EDX. The compressive strength, pH, Ca ion release, and solubility were measured, and antibacterial activity was tested. The results showed a spherical shape of the synthesized CuNP with a particle size of 28.08 nm. Adding CuNP-9 to hydrated MTA increased the compressive strength, pH, Ca ion release, and solubility, with the value of 4.78±0.38 MPa; 9.01±0.03; 1718±63 ppm, and 22.48±0.37%, respectively. The highest antibacterial activity occurred for Cu-MTA-9, with an inhibition zone of 10.15±0.47 mm against S. aureus and 11.93±1.16 mm against P. aeruginosa. The findings show a potential application of the product for endodontic materials containing antibacterial agents.